Management of Acute Mastoiditis With Immediate Needle Aspiration for Subperiosteal Abscess. Issue 6 (July 2019) - Bartov, Noam; Lahav, Yonatan; Lahav, Gil; Zloczower, Elchanan; Katzenell, Udi; Halperin, Doron; Hilly, Ohad; Shoffel-Havakuk, Hagit
Abstract : Objectives: The management of children with acute mastoiditis (AM) is still debated. Some advocate computed tomography (CT) and cortical mastoidectomy (CM) for all cases while others favor a more conservative management. This study assesses the safety and outcome of a conservative management scheme, with immediate myringotomy and postauricular needle aspiration (PANA) of a subperiosteal abscess (SPA). Methods: A retrospective cohort of children with AM younger than 12 years admitted to our institute between 1999 and 2017. Data collection includes patient characteristics, signs and symptoms, physical examination, laboratory tests, treatment regime, imaging findings, and long-term outcomes. Results: The study included 283 children. Ninety-eight children (34.6%) had a suspected SPA on admission and underwent a trial of immediate PANA, and 56.1% (55 cases) were positive. Of these 55, 83.6% (46) did not require CM. Twenty-four additional children had an SPA, proven by CT or during surgery, bringing the total SPA cases to 79 (27.9%). Of all children with proven SPA, 70.9% (56) did not require CM, with the practiced conservative management sufficing. Intracranial complication rates were 4.9% (14) and 8.8% (25) underwent CM. Long-term follow-up was available for 250 children. One child had hearing loss with a bilateral mixed hearing loss (50 decibels). There were no cases of neurological sequela. Conclusions: Conservative management of AM, involving prompt myringotomy for all patients and PANA for SPA, is safe and effective, and reduces the need for CT and CM. Conservative management obviates unnecessary radiation, general anesthesia, and surgery, without increasing the risk of immediate or long-term complications. Abstract : Supplemental Digital Content is available in the text